2020
DOI: 10.3390/biom10020286
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylaspartate Is an Important Brain Osmolyte

Abstract: Most of the human diseases related to various proteopathies are confined to the brain, which leads to the development of various forms of neurological disorders. The human brain consists of several osmolytic compounds, such as N-Acetylaspartate (NAA), myo-inositol (mI), glutamate (Glu), glutamine (Gln), creatine (Cr), and choline-containing compounds (Cho). Among these osmolytes, the level of NAA drastically decreases under neurological conditions, and, hence, NAA is considered to be one of the most widely acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…The increase in nitrogen-rich metabolites in serum may translate to the brain through the BBB, increasing amino acids synthesis in the hippocampus (e.g., serine) and decreasing the concentration of brain osmolytes (e.g., NAA). The level of hippocampal NAA has been noted in several human brain disorders ( 34 , 35 ). Even though its functional roles remain unclear, it is believed to be involved in neuromodulation, which is supported by one interpretation of the results presented here.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in nitrogen-rich metabolites in serum may translate to the brain through the BBB, increasing amino acids synthesis in the hippocampus (e.g., serine) and decreasing the concentration of brain osmolytes (e.g., NAA). The level of hippocampal NAA has been noted in several human brain disorders ( 34 , 35 ). Even though its functional roles remain unclear, it is believed to be involved in neuromodulation, which is supported by one interpretation of the results presented here.…”
Section: Discussionmentioning
confidence: 99%
“…It has been known from various studies that NAA is an osmolyte in the brain cells responsible for the removal of water from neurons (Taylor et al, 1994(Taylor et al, , 1995. Most recently, our laboratory also reported that NAA exhibit strong stabilizing effect on different proteins (due to increase in T m and G D • ) (Warepam et al, 2020). Furthermore as mentioned above, there is alteration in the NAA levels under various neurodegenerative conditions.…”
Section: Introductionmentioning
confidence: 52%
“…The increase in nitrogen-rich metabolites in serum may translate to the brain through the BBB, increasing amino acids synthesis in hippocampus (e.g., serine) and decreasing the concentration of brain osmolytes (e.g., NAA). The level of hippocampal NAA has been noted in several human brain disorders 34,35 . Even though its functional roles remain unclear, it is believed to be involved in neuromodulation, which is supported by one interpretation of the results presented here.…”
Section: Discussionmentioning
confidence: 99%